2018
DOI: 10.1103/physrevlett.120.018101
|View full text |Cite
|
Sign up to set email alerts
|

Immotile Active Matter: Activity from Death and Reproduction

Abstract: Unlike equilibrium atomic solids, biofilms-soft solids composed of bacterial cells-do not experience significant thermal fluctuations at the constituent level. However, living cells stochastically reproduce and die, provoking a mechanical response. We investigate the mechanical consequences of cellular death and reproduction by measuring surface-height fluctuations of biofilms containing two mutually antagonistic strains of Vibrio cholerae that kill one another on contact via the type VI secretion system. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…This was later confirmed by similar studies of shape fluctuations exhibited by large lipid vesicles ( Schneider et al, 1984 ). The generalization of these considerations to homeostatic tissues with cell division, rearrangements and apoptosis has also been considered ( Risler et al, 2015 ; Kalziqi et al, 2018 ). While such membrane systems may differ greatly in the specific values of their elastic modulus (and, indeed, of their microscopic membrane constituents), the viscosity of the surrounding fluid, and their physical size, the space-time correlation function of fluctuations about the equilibrium shape adopts a universal form in appropriately rescaled length and frequency variables.…”
Section: Discussionmentioning
confidence: 99%
“…This was later confirmed by similar studies of shape fluctuations exhibited by large lipid vesicles ( Schneider et al, 1984 ). The generalization of these considerations to homeostatic tissues with cell division, rearrangements and apoptosis has also been considered ( Risler et al, 2015 ; Kalziqi et al, 2018 ). While such membrane systems may differ greatly in the specific values of their elastic modulus (and, indeed, of their microscopic membrane constituents), the viscosity of the surrounding fluid, and their physical size, the space-time correlation function of fluctuations about the equilibrium shape adopts a universal form in appropriately rescaled length and frequency variables.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that physical effects observed in studies of lateral range expansions [67][68][69][70] also play a role in the upward growth of unconfined biofilms. Previous studies found that proliferating cells in crowded environments interact mechanically [71][72][73], pushing cells towards the expanding cell front. In analogy, during vertical biofilm growth, the few labelled, non-killer cells may be mechanically pushed off the agar surface by neighbouring cells that proliferate.…”
Section: Limited Invasion Via Contact Killingmentioning
confidence: 99%
“…Biofilms are responsible for most clinical infections [8] and related processes, such as biofouling, are costly to industry [9]. Central to this mode of growth is the ability of bacteria to coordinate behavior and act as a multicellular organism [5][6][7][10][11][12]. Therefore, understanding biofilm regulation is important in trying to control or prevent biofilm formation.…”
Section: Introductionmentioning
confidence: 99%